ANALISA SIFAT FISIS SENSOR KOIL DATAR DENGAN VARIASI GEOMETRI - Roberto, R.; Umar, L.; Setiadi, R. N. (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Flat coil inductive sensors based on Eddy currents principal could work without directmechanical contact on the object, it could work continuously and reactively to theconductive material. This system is easily influenced by external disturbances. Based oninductance value due to changes in magnetic force lines that occurs between the sensorand conductor material (disturbances material). The system could be used as a detectionof distance translation. The used sensors in this study was a flat coil made of PrintedCircuit Board (PCB) technology with various geometric shapes, such as circle, square,rectangle and octagonal. Distance detection analysis were evaluated using a LCoscillator which was directly connected to a computer that able to transform a massiverange measurement into frequencies. Characteristics of distance detection wasinfluenced by geometry of the flat coil sensors with its highest value of frequency of1.68 MHz for a circular shape, 1.66 MHz for an octagonal shape, 1.52 MHz for ansquare shape, 1.42 MHz for an rectangular shape, respectively with the minimumdistances as far as 5 mm for each shape. The temperature tested as external disturbancescaused change in characteristics of the transfer curve based on drift frequency fordistance detection analysis based on a mathematical formula.